SUNDA WIWITAN ON PARAHYANG LAND - Abdurrahman Misno Bambang Pawiro (Al-Albab, 2014)
The arrival of the great religions of the world to Indonesia did not eliminate existing local beliefs/religions of its people. The followers of the local beliefs remained strong in the midst of the spread of the great religions. Although those religions did not eliminate the local beliefs, they in fact had a significant influence on them. Sunda Wiwitan is one of the local beliefs that until today is still parcticed by the Baduy Community in Kanekes Village, Leuwidamar Sub-district, Lebak District of Banten Province. The Baduy people to this day have not embraced any major religions of the world. They are still consistent with the Sunda Wiwitan, believed to be the old legacy of their Sunda ancestors that become their karuhun. The current Sunda Wiwitan belief has been heavily influenced by Hinduism and Islam. Hindu influence gave rise to the concept of gods in their belief, while the influence of Islam gave rise to the terms Allah as God, Adam Tunggal, Adam and Eve, the Shahada (Profession) of Prophet Muhammad, Circumcision, Shahada in marriages. Even mantras recited by the puun also derived a lot of terms from Islam. Keywords: Sunda Wiwitan, Local Belief, Baduy, Parahyang, Banten.